Review of Chapter 3, “John Paul II and Christian-Jewish Reconciliation.” Karma Ben-Johanan’s "Jacob’s Younger Brother: Christian-Jewish Relations after Vatican II" - Destivelle, Hyacinthe (Studies in Christian-Jewish Relations, 2023)
No abstract is available.